A rare case of giant peritoneal loose body: A case report - Dhola, Dilip; Banerjee, Divya Jyoti; Shah, Viral (Indian Journal of Case Reports, 2024)
Peritoneal loose bodies (PLBs) are uncommon abdominal lesions, typically asymptomatic and discovered incidentally during surgery. Giant PLBs, exceeding 5 cm in size, are even rarer and can present with clinical symptoms mimicking other abdominal pathologies. We present a 57-year-old male with a giant PLB presenting as intermittent abdominal pain, distention, and rectal bleeding. Imaging studies suggested colo-colic intussusception due to a colonic lipoma. The patient underwent an exploratory laparotomy revealing a segment of the descending colon containing multiple lipomas, one causing intussusception. In addition, a separate giant PLB 6 × 5.5 cm with central calcification was identified. A segmental colectomy with primary anastomosis and resection of the PLB was performed. The patient recovered well and reported complete resolution of symptoms at follow-up. Pathology confirmed a benign lipoma and a giant PLB. This case highlights the potential for giant PLBs to cause clinical symptoms and emphasizes the importance of including them in the differential diagnosis of abdominal complaints, even in the absence of a classic presentation. Exploratory laparotomy remains a definitive approach for diagnosis and management in such cases.